The Eighth Grade Students’ Ability of Using Adverbs in Descriptive Writing - Agry Tafuli; Anselmus Sahan; Maria W. Wisrance (Indonesian Educational Research Journal, 2024)
This study aims to find out whether or not the students able to use adverbs, their level of mastery and the difficult types of adverbs in writing descriptive text. To attain the goals of this research, it employed a qualitative research method, 14 eighth grade students of SMP Negeri Tublopo chosen as its samples, and a writing test. To get the data needed, it explained its aims, kinds of adverbs and ways of writing descriptive text, and asked them to write at least 3 paragraphs of descriptive text by using the prepared topic. The worksheets were counted and cored by the right answers divided with the total number of students times 100% in order to categorize and identify their ability. Their scores were then ranged from 46-100 in order to categorize their level of ability (from poor to excellent). The results show that they have mastered the use of kinds of adverbs in their writing since they got 80 average score, above the maximum mastery criteria. However, adverb of degree is still the most difficult type for them to master. Therefore, their level of mastery is categorized excellent since eight students (57.14%) got scores ranged from 80-100. It implies that teachers should develop their students’ ability by forcing them to use adverbs in writing.